Seasonal Cycle of Sea Surface Salinity in the Angola Upwelling System. Issue 7 (30th June 2022) - Awo, F. M.; Rouault, M.; Ostrowski, M.; Tomety, F. S.; Da‐Allada, C. Y.; Jouanno, J.
Abstract: The seasonal cycle of sea surface salinity (SSS) along the Angolan coast is investigated using observations and a regional ocean model. The model reproduces the main characteristic of the seasonal cycle of SSS along the Angolan coast, such as the freshwater discharge signature off the Congo River plume and the low‐salinity observed in February/March and October/November along the Angolan coast. The model also reproduces the two maxima of salinity in June/July and December/January. The analysis of the model salt budget reveals that the semi‐annual cycle of SSS is controlled by the meridional advection of surface water, the vertical advection of subsurface water, and the mixing at the base of the mixed layer. The meridional advection is controlled by the Angola Current which brings low‐salinity water from offshore region of the Congolese coast toward the south Angolan coast in February/March and October/November. The vertical advection contribution is modulated by the vertical stratification of salinity and not by vertical velocities which peak during the main Angolan upwelling season. The vertical stratification is due to the low‐salinity intrusion at the Angolan coast that creates a strong vertical salinity gradient with low‐salinity at the surface and high salinity at the subsurface. Plain Language Summary: Ocean salinity is a key driver of oceanic circulation, and it affects profoundly the marine coastal ecosystem. We study here the seasonal cycle of the upper ocean salinity off the Angolan coast. We observe a low‐salinity water intrusion in February/March and October/November along the Angolan coast. We find the low‐salinity intrusion due to the well‐known Angola Current that brings low‐salinity waters from the Congo River plume southward. On its way south along the Angola coast, surface water gains salt from subsurface water that rises to the surface through upwelling and mixing at the base of the ocean surface mixed layer. Key Points: The surface salinity along the Angolan coast presents a semi‐annual cycle The Angola Current drives the low‐salinity intrusion at the Angolan coast while subsurface processes bring salty water toward the surface The low‐salinity intrusion at the Angolan coast creates a strong vertical salinity gradient that favors vertical salt advection